Central banks in parliaments: A text analysis of the parliamentary hearings of the Bank of England, the European Central Bank and the Federal Reserve - Nicolò Fraccaroli; Alessandro Giovannini; Jean-François Jamet (European Central Bank (ECB), 2020)
As the role of central banks expanded, demand for public scrutiny of their actions increased. This paper investigates whether parliamentary hearings, the main tool to hold central banks accountable, are fit for this purpose. Using text analysis, it detects the topics and sentiments in parliamentary hearings of the Bank of England, the European Central Bank and the Federal Reserve from 1999 to 2019. It shows that, while central bank objectives play the most relevant role in determining the topic, unemployment is negatively associated with the focus of hearings on price stability. Sentiments are more negative when uncertainty is higher and when inflation is more distant from the central bank's inflation aim. These findings suggest that parliamentarians use hearings to scrutinise the performance of central banks in line with their objectives and economic developments, but also that uncertainty is associated with a higher perceived risk of under-performance of central banks.
Keywords: E02; E52; E58; 330; Central Bank Accountability; Monetary Policy; Uncertainty; Text Analysis